Left Atrial Volume Index Is Associated With Cardioembolic Stroke and Atrial Fibrillation Detection After Embolic Stroke of Undetermined Source. Issue 8 (August 2019) - Jordan, Kevin; Yaghi, Shadi; Poppas, Athena; Chang, Andrew D.; Mac Grory, Brian; Cutting, Shawna; Burton, Tina; Jayaraman, Mahesh; Tsivgoulis, Georgios; Sabeh, M. Khaled; Merkler, Alexander E.; Kamel, Hooman; et al.
Abstract : Background and Purpose—: Left atrial enlargement has been shown to be associated with ischemic stroke, but the association with embolic stroke mechanisms remains unknown. We aim to study the associations between left atrial volume index (LAVI) and embolic stroke subtypes and atrial fibrillation (AF) detection on cardiac event monitoring in patients with embolic stroke of unknown source. Methods—: Data were collected from a prospective cohort of consecutive patients with ischemic stroke admitted to a comprehensive stroke center over 18 months. Stroke subtype was classified into cardioembolic stroke, noncardioembolic stroke of determined mechanism (NCE), or embolic stroke of undetermined source (ESUS). Univariate and prespecified multivariable analyses were performed to assess associations between LAVI and stroke subtype and AF detection in patients with ESUS. Results—: Of 1224 consecutive patients identified during the study period, 1020 (82.6%) underwent transthoracic echocardiography and had LAVI measurements. LAVI was greater in patients with cardioembolic stroke than NCE (41.4 mL/m 2 ±18.0 versus 28.6 mL/m 2 ±12.2; P <0.001) but not in ESUS versus NCE (28.9 mL/m 2 ±12.6 versus 28.6 mL/m 2 ±12.2; P =0.61). In multivariable logistic regression models, LAVI was greater in cardioembolic stroke versus NCE (adjusted odds ratio per mL/m 2, 1.07; 95% CI, 1.05–1.09; P <0.001) but not in ESUS versus NCE (adjusted odds ratio per mL/m 2, 1.00; 95% CI, 0.99–1.02; P =0.720). Among 99 patients with ESUS who underwent cardiac monitoring, 18.2% had AF detected; LAVI was independently associated with AF detection in ESUS (adjusted odds ratio per mL/m 2, 1.09; 95% CI, 1.02–1.15; P =0.007). Conclusions—: LAVI is associated with cardioembolic stroke as well as AF detection in patients with ESUS, 2 subsets of ischemic stroke that benefit from anticoagulation therapy. Patients with increased LAVI may be a subgroup where anticoagulation may be tested for stroke prevention.